REKONSTRUKSI PENERAPAN QAWĀ‘ID AL-FIQHIYYAH DALAM PENETAPAN HAK NAFKAH PASCA PERCERAIAN DI INDONESIA - Muslimat (JOURNAL OF LAW AND NATION, 2026)
The determination of post-divorce maintenance rights in Indonesia is one of the key aspects of Islamic family law, aimed at ensuring the protection of former wives and children following the dissolution of marriage. Judicial practice shows that judges do not merely rely on the normative provisions of legislation, but also apply the principles of Islamic law contained in the qawā‘id al-fiqhiyyah. However, the application of these fiqh principles remains partial and has not yet been established within a systematic methodological framework. This article aims to reconstruct the application of qawā‘id al-fiqhiyyah in determining post-divorce maintenance rights in Indonesia through a normative-conceptual approach. This study employs a normative legal research methodology, which aims to examine applicable legal principles, particularly those relating to maintenance from the perspective of qawā‘id al-fiqhiyyah. The findings indicate that principles such as the need to eliminate harm, the principle that difficulty gives way to ease, the use of custom as a legal basis, and the requirement that the ruler’s policies be oriented towards the public interest can serve as a foundation for reconstructing the determination of iddah maintenance, mut’ah, madhiyah, and child maintenance. It is hoped that this reconstruction will lead to rulings that are fairer, more responsive, and focused on protecting women’s rights following divorce.